2017
DOI: 10.25002/tji.2017.573
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Propolis Extract on Population of IL-10 and TGF-β Expression in CD4+CD25+ Regulatory T Cells in DMBA-induced Breast Cancer in Female Sprague-Dawley Rats

Abstract: Introduction: The aim of this study was to investigate the effect of propolis extract to the population of regulatory T cells (CD4 + CD25 + FoxP3 + ) expressing IL-10 and TGF-β in vivo (DMBA-induced breast cancer in Female SpragueDawley Rats).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(11 reference statements)
0
4
0
2
Order By: Relevance
“…There is also evidence that propolis affects immune response in the presence of breast cancers. 66 Kusnul et al 96 reported that propolis significantly reduced the relative number of CD4+, CD25+, FoxP3+ regulatory T cells expressing IL-10 and TGF-β in mice with breast cancer. The suppression of IL-10, which is an immunosuppressive cytokine, is thought to be beneficial in treating cancers.…”
Section: Cytotoxicity Against Breast Cancer Cellsmentioning
confidence: 99%
“…There is also evidence that propolis affects immune response in the presence of breast cancers. 66 Kusnul et al 96 reported that propolis significantly reduced the relative number of CD4+, CD25+, FoxP3+ regulatory T cells expressing IL-10 and TGF-β in mice with breast cancer. The suppression of IL-10, which is an immunosuppressive cytokine, is thought to be beneficial in treating cancers.…”
Section: Cytotoxicity Against Breast Cancer Cellsmentioning
confidence: 99%
“…8 Secara in vivo ekstrak propolis juga telah dibuktikan mampu meningkatkan respon imun anti kanker pada tikus Spraque-Dawley yang diinduksi mengalami kanker payudara dengan menggunakan DMBA. 10 Selain itu keamanan penggunaan ekstrak propolis terhadap organ ginjal dan hepar juga telah diuji dengan uji toksisitas subkronik pada tikus wistar dan hasilnya menunjukkan bahwa ekstrak propolis aman untuk dikonsumsi (data belum dipublikasi). nyata.…”
Section: Pendahuluanunclassified
“…Dalam dunia pengobatan, propolis sudah digunakan sejak dahulu kala dan hingga kini telah diketahui propolis bisa menjadi obat alami dengan kemampuan anti bakteri (Hasson, 2014), anti tumor (Borges et al, 2011;Khacha-ananda et al, 2013), antioksidan (Padmavathi et al, 2006), dan imunomodulator (Sforcin, Kaneno dan Funari, 2011;Kusnul et al, 2017).…”
Section: Pendahuluanunclassified